Pagewell 2.0 : using customer research for product development - Sawhney, Mohanbir S., (SAGE knowledge. Cases., 2016)
PageWell, an e-reading platform provider, was preparing to launch PageWell 2.0 to the larger full-time MBA student market after a successful trial of PageWell 1.0 in Executive MBA (EMBA) classes at the Kellogg School of Management. Research had shown that full-time MBA students would be very interested in using products that allowed electronic access to course materials everywhere and across many platforms and that allowed electronic note-taking and storage. This case examines how PageWell addressed the challenge of delivering these new features.